2010
DOI: 10.1111/j.1651-2227.2010.02047.x
|View full text |Cite
|
Sign up to set email alerts
|

Fathers’ involvement in Swedish child health care – the role of nurses’ practices and attitudes

Abstract: Fathers received less support from child health nurses, and many nurses were ambivalent about fathers' caring abilities. Methods need to be developed to involve both parents in child health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(78 citation statements)
references
References 19 publications
2
71
0
5
Order By: Relevance
“…This is consistent with earlier research on nurses' views of fathers as the secondary and mothers as the primary parent . Massoudi, Wickberg and Hwang found that fathers receive less encouragement to visit the CHCs compared to mothers and that the nurses did not know how to handle fathers who might need more support. This research expanded on Massoudi et al.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This is consistent with earlier research on nurses' views of fathers as the secondary and mothers as the primary parent . Massoudi, Wickberg and Hwang found that fathers receive less encouragement to visit the CHCs compared to mothers and that the nurses did not know how to handle fathers who might need more support. This research expanded on Massoudi et al.…”
Section: Discussionsupporting
confidence: 88%
“…Nurses were considered to be in the precontemplation stage because they did not think that fathers' lower engagement in the CHC was an issue and hence did not think that any action on their part was required to encourage paternal participation in the CHCs. Nurses in the precontemplation stage were unaware that by not directly encouraging paternal participation, fathers may feel unsupported and further disassociate themselves from the CHCs , leaving fathers uninformed about their child's growth and development. The nurses regarded mothers as primary parents with an emphasis on mothers' breastfeeding of and attachment to the infant, whereas the father was assigned a supportive role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that although CHS nurses appreciate working with both parents, they do not feel they have the same competencies, time or resources to offer them proper support . CHS nurses experienced how this extra interview would allow them greater insight into the families and enable them to support both children and parents in better ways.…”
Section: Discussionmentioning
confidence: 99%
“…Contudo, alguns autores Rev Bras Enferm. 2014 nov-dez;67(6):957-64. afirmam que apesar de os pais terem competência para atuar no cuidado, a maior parte da responsabilidade com as tarefas básicas é assumida pela mãe (14) . A totalidade dos pais desse estudo referiram a utilização de estruturas de apoio em alguma etapa do desenvolvimento dos filhos.…”
Section: Discussionunclassified